Investigasi Aktivitas Lindung Nilai, Ukuran Perusahaan dan Leverage terhadap Kinerja Keuangan - Sari, Nada Kania; Mahardika, Dewa Putra Krishna (SAFE-Network, 2023)
The financial performance of a company is an overview of company achievement in company operations during a certain period. One of the sources that can be reviewed is from financial report so that the things that the company does can be monitored and it can be measured by the amount of net profit over a certain period of time. Therefore, there is a net profit target that must be fulfilled by the company and the company can implement certain strategies to reach good financial performance. The study aimed was to find out the influence of hedging activities measured with the dummy variable, Ln Asset Total measured by firm size, and leverage Debt to Equity Ratio that is measured and proxied by Return on Asset in coal companies from 2017 to 2021 listed on the Indonesia Stock Exchange. The coal industries listed was from 2017 to 2021 comprised the study’s sample. 15 companies were as the samples for this study since a five-year period. Eviews 12 was a data analysis method for examining regression of panel data. And then, secondary data was selected in the form of company financial statements. As a result, hedging activities, company size and financial performance is significantly effected by leverage. Secondary data in the form of financial statements from companies served as the cornerstones for the analysis. The results revealed that hedging activities, firm size, and leverage simultaneously had a significant influence on financial performance. Partially, hedging activities and firm size had significantly positive influence on financial performance. Meanwhile, leverage partially had significantly negative influence on financial performance.